Metode Potensial Untuk Menghitung Clock Skew - I Gede Agus Aditya Putra Aditya; Komang Oka Saputra; Ni Made Ary Esta Dewi Wirastuti (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2022)
Some studies such as Aoki measure clock skew by filtering outliers by selecting the minimum offset that is collected using linear regression to calculate the slope of the accumulated minimum offset. Huang who uses the QPM (Quick Piecewise Minimum) algorithm to calculate the skew of the minimum offset at the beginning and end of the collected offsets and Moon's research that uses the LPA (Linear Programming Algorithm) algorithm which determines the clock skew of the line gradient that is below the offset. In addition, there are several methods that have the potential to be used in measuring clock skew including ant colony, bee colony, particle swarm, and also genetic algorithm. From these several methods, one method that has potential as a method that can be used for measuring clock skew will be selected. The method that can be used is particle swarm optimization because it is considered more efficient and flexible and easy to implement with few parameters used.